Omentoplasty to reduce anastomotic leak in colorectal surgery: a meta‐analysis. Issue 7 (15th February 2022) - Sahebally, Shaheel Mohammad; Chan, Erick; Azmir, Alisha; Lu, Cu Tai; Doudle, Mark; Naik, Arun; Nolan, Gregory; Von Papen, Michael
Abstract: Background: Anastomotic leaks (AL) remain a devastating complication following intestinal anastomoses resulting in increased morbidity and mortality. Wrapping the anastomosis with omentum may be protective although data are conflicting. We performed a meta‐analysis to assess the effect of omentoplasty on colorectal anastomoses. Methods: PubMed, EMBASE and Cochrane databases were searched for relevant articles from inception until August 2021. All randomized controlled trials (RCT) that reported on the use of omentoplasty in colon and rectal surgery were included. The primary outcome was rate of overall AL while secondary outcomes included clinical and radiological AL, overall reoperation and mortality. Random effects models were used to calculate pooled effect size estimates. Sensitivity analyses were also performed. Results: Four RCTs were included capturing 1067 patients. The mean (SD) age of the cohort was 61.5 (±14.8) years. On random effects analysis, omentoplasty reduced rate of overall (OR 0.43, 95% CI = 0.21–0.87, p  = 0.02) and clinical AL (OR = 0.35, 95% CI = 0.15–0.81, p  = 0.01). However, there was no difference in radiological AL (OR = 0.77, 95% CI = 0.40–1.47, p  = 0.42), overall reoperations (OR 0.48, 95% CI = 0.18–1.32, p  = 0.16) or mortality (OR 0.52, 95% CI = 0.12 to–2.18, p  = 0.37). On sensitivity analysis, assessing rectal anastomoses only, the results for overall AL remained similar (OR 0.28, 95% CI = 0.12–0.61, p  = 0.002). Conclusion: Although omentoplasty appears to reduce the rate of overall and clinical AL, the heterogeneity in the data prevents definitive recommendations from being made. Further well‐designed trials are needed to investigate this technique. Abstract : Covering a colorectal anastomosis with omentum may be beneficial although it is not standard practice due to conflicting data. The current study summarizes all the available evidence on omentoplasty in colorectal surgery and demonstrates that it reduces overall and clinical leak rates. Further studies are needed to confirm these findings.